2010
DOI: 10.1097/mnm.0b013e3283355c8b
|View full text |Cite
|
Sign up to set email alerts
|

The effect of recombinant human TSH on 123I thyroid uptake after intravenous iodide contrast agent

Abstract: It was shown that a single dose of 0.1 mg of rhTSH, given 96 h after the exposure to computed tomography iodinated contrast media, enhances the RAIU in nine euthyroid patients 4 h after 123I administration. These results indicate that rhTSH could be useful for avoiding delay in the treatment of patients with 131I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
2
1
Order By: Relevance
“…The effect of ICM on TSH-induced iodide uptake by the thyroid is not well-documented. A clinical study reported that the inhibition of iodide uptake by the thyroid could be reversed by intramuscular administration of recombinant human TSH [38]. However, the ICM stunning reported in this study was relatively low and a large heterogeneity was observed in the nine patients of the cohort [38].…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…The effect of ICM on TSH-induced iodide uptake by the thyroid is not well-documented. A clinical study reported that the inhibition of iodide uptake by the thyroid could be reversed by intramuscular administration of recombinant human TSH [38]. However, the ICM stunning reported in this study was relatively low and a large heterogeneity was observed in the nine patients of the cohort [38].…”
Section: Discussioncontrasting
confidence: 54%
“…A clinical study reported that the inhibition of iodide uptake by the thyroid could be reversed by intramuscular administration of recombinant human TSH [38]. However, the ICM stunning reported in this study was relatively low and a large heterogeneity was observed in the nine patients of the cohort [38]. In another study, the anecdotic case of a patient with differentiated thyroid carcinoma and who had previously received ICM was reported.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation